Current State and Development Prospects of the Russian Factoring Market (Brief Statistical Analysis) - Lyubov Yu. Arkhangelskaya; Viktor N. Salin (Статистика и экономика, 2021)
Factoring is a fairly new way for Russia to finance the accounts payable and receivable of business structures by specialized companies or credit institutions and their divisions (Factors) against the assignment of claims against one of the parties (buyer or seller) of a sale and purchase transaction of products or property to a third party (Factor) is currently developing at a high pace. On average, according to sample data for 2011 -2019 the annual growth rate of the volumes of financing of accounts payable and receivable of companies in Russia due to factoring operations increased by 20%, which in absolute terms amounted to 303.3 billion rubles, and reached by 2019 - 3.5 trillion rubles.However, there is still no established definition of this economic category in the Civil Code of the Russian Federation. In the scientific and educational foreign and domestic literature there are somewhat contradictory interpretations of the classifications of the types of factoring, there is no legislatively established system of statistical indicators characterizing this segment of the financial intermediation services market. The lack of a developed regulatory framework for regulating relations in this market segment slows down its development, necessitates improving both Russian legislation and methodological support for a comprehensive statistical analysis of the state and development of this market segment. In this regard, the purpose of this study is to develop a methodology for a comprehensive statistical analysis of the market segment of financial intermediation services, to determine the prevailing sectoral, territorial and types of proportions related to the scale of business of the parties to the factoring agreement in this market segment using the statistical methodology for analyzing the series of dynamics and attributive groupings of the main indicators characterizing the state and development of the Russian factoring market. Based on the theoretical analysis, the author’s interpretation of the content of the economic category “factoring” is given, a system of indicators is proposed that characterizes factoring as a type of financial intermediation services (object of research), based on the development of the Association of factoring companies, Rosstat, expert agencies (for example, “Expert RA”); the features of the formation of statistical groupings (series: attributive, variation, dynamics) for various purposes of analyzing the market of factoring services are revealed, the author’s method of complex statistical analysis of any segment of the financial intermediation services market, which is the subject of research, is presented. The results of approbation of the methodology for a comprehensive statistical analysis of the Russian factoring market based on sample data for 2011 – 2019 are presented, conclusions are drawn about the dynamics of the main indicators of the factoring market development, structural shifts and changes in proportions in this market segment, a forecast of expected changes in the Russian factoring market for  2021 is made, incl. and influenced by the Covid-19 pandemic.The results of this study are aimed at developing a methodology for a comprehensive statistical analysis of factoring as a segment of the financial intermediation services market, including for the purposes of international comparisons of indicators of the state and development of the Factors and their clients.They can be useful to the professional community of factoring companies (Factors), business structures - consumers of factoring services, and also be used in educational activities in the preparation of financial specialists in economic universities of the country.